The nomenclature of the blond capuchin, Cebus flavius (Schreber, 1799) (Mammalia, Primates, Cebidae) - Zijlstra, Jelle S. (Zootaxa, 2020)
I review the nomenclatural history of the blond capuchin, Cebus flavius (Schreber), a Brazilian monkey species. The name was published in 1799, not 1774 as generally cited, so the species is correctly known as Cebus flavius (Schreber, 1799).